A clinical protocol for group-based ketamine-assisted therapy in a community of practice: the Roots To Thrive model - Dames, Shannon; Kryskow, Pamela; Tsang, Vivian W. L.; Argento, Elena (Frontiers in Psychiatry, 2025)
BackgroundKetamine-assisted therapy (KaT) has demonstrated therapeutic potential in treating depression, anxiety, and PTSD, driving interest in group-based models of care. Yet, few published protocols offer the comprehensive structure required for safe, scalable application in real-world clinical settings. The RTT-KaT model offers a resilience-informed, community-anchored framework that integrates trauma-aware care with a respectful and intentional weaving of Western and Indigenous knowledge systems. Initially launched as a quality improvement initiative through a partnership between a Canadian university and a regional health authority, RTT-KaT has since evolved into a non-profit clinical program. To date, it has supported over 750 participants through more than 2,000 KaT sessions and 700 Community of Practice groups. RTT-KaT is a culturally informed, resilience-focused model of group-based psychedelic-assisted therapy developed and refined since 2018. The model is rooted in the intentional weaving of Western clinical frameworks and Indigenous knowledge systems, grounded in principles of relational accountability, cultural humility, and trauma-informed care.MethodsThis methods protocol describes the RTT-KaT model, including its medical, operational, and ceremonial components. Delivered over 12 weeks, the program embeds three intramuscular or sublingual ketamine sessions within a structured Community of Practice. Weekly large- and small-group sessions are grounded in somatic, relational, and culturally responsive principles. The program is co-facilitated by a multidisciplinary—and often multicultural—team including healthcare providers, therapists, and somatic energy practitioners. A structured, psychology- and resilience-informed curriculum cultivates core resilience factors—such as congruence and sense of coherence—through practices that foster awareness, meaning-making, somatic regulation, and alignment with one’s values and purpose.ResultsKetamine is positioned as an amplifier, not the primary driver of change. Ceremonial framing, intentional group process, and a relationally anchored curriculum serve as central mechanisms supporting meaningful change. Supplementary materials detail protocols for screening, dosing, consent, medical monitoring, and integration. While early outcome data have been published elsewhere, this article presents the methodology and protocol to support replication, adaptation, and ongoing evaluation.DiscussionRTT-KaT offers a structured, scalable, evidence-informed, and culturally responsive model that bridges clinical safety with both Western and Indigenous knowledge systems. A longitudinal follow-up study is currently underway to evaluate long-term impact and guide future implementations.